”Labour conflicts before and after political and economic reforms in Algeria: Field study at” Ferovial” company in the city of ” Annaba - BERROUK, TAREK BRIK (Journal of Humanities & Social Sciences, 2019)
The subject of labour conflicts from the important places that attracted the attention of many scientists and researchers in all disciplines, especially scholars of the meeting organization and work, religion cared for and studied and treated from many angles,So as to know the causes of conflicts in institutions and from there try to eliminate them even relatively.This phenomenon also forms the intersection of many sciences, such as sociology, psychology, and organizationAnd legal sciences. Therefore, this study seeks to identify the actual reality of labor conflicts.The study concluded with a major result:The labour conflicts within the Algerian industrial establishment are mainly due to economic disputes, most of which revolve around wages(42.30%), promotions(05.60%), working conditions(47.90%)... Based on this, we had to put forward a set of recommendations that would contribute to reducing these conflicts within the institution:• The need to provide a calm social environment of understanding, security and stability for the benefit of all.• Justice in the promotion policy within the institution in accordance with legal standards that are set in advance.• The need to involve workers in the decision-making process within the institution.
Keywords: conflict; work; reforms; institution